Commercially speaking : teacher's book - Irvine, Mark.; Cadman, Marion (Oxford : Oxford University Press, 1999)
The situation. Letter layout. Peter phones Teresa. Places. Formality and informality. Travel arrangements. The shop. Good commercial letters. Getting through. At a trade fiar. A letter of enquiry. Messages...
Keywords: English language; Business English; English composition; Commercial correspondence; Commercial correspondence; English language -- Business English; English language -- Composition and exercises